2021
DOI: 10.3389/fonc.2021.704475
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of the Continuous Administration of Anti-PD-1 Antibody via Continuation or Rechallenge After the Occurrence of Immune-Related Adverse Events

Abstract: ObjectivesAlthough immune checkpoint inhibitors (ICIs) have been shown to improve overall survival (OS) in advanced non-small-cell lung cancer (NSCLC) patients, ICIs sometimes cause various types of immune-related adverse events (irAEs), which lead to the interruption of ICI treatment. This study aims to evaluate the clinical significance of the continuation of ICIs in NSCLC patients with irAEs and to assess the safety and efficacy of the readministration of ICIs after their discontinuation due to irAEs.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…36 In some patients, it is feasible to consider ICI rechallenge after irAE remission, even if same or new toxicities occur, as most secondary irAEs are not more severe than the initial irAEs and could be manageable. 37,38 In our study, we found that the incidence of the second irAE in patients who underwent ICI rechallenge was 44.8% (13/29), which aligns with the incidence reported in previous studies. 39 Patients with initial irAEs of gastrointestinal toxicity (2/2), cardiovascular toxicity (1/1), and pneumonitis (5/10) were more prone to developing secondary irAEs.…”
Section: Discussionsupporting
confidence: 91%
“…36 In some patients, it is feasible to consider ICI rechallenge after irAE remission, even if same or new toxicities occur, as most secondary irAEs are not more severe than the initial irAEs and could be manageable. 37,38 In our study, we found that the incidence of the second irAE in patients who underwent ICI rechallenge was 44.8% (13/29), which aligns with the incidence reported in previous studies. 39 Patients with initial irAEs of gastrointestinal toxicity (2/2), cardiovascular toxicity (1/1), and pneumonitis (5/10) were more prone to developing secondary irAEs.…”
Section: Discussionsupporting
confidence: 91%
“…Sixteen studies (8,9,(17)(18)(19)(20)(21)(23)(24)(25)(26)(27)(28)(29)31,32) were enrolled in the analysis of efficacy of ICIs retreatment. The pooled ORR and DCR of ICIs retreatment were respectively 20% and 54% (Table 2).…”
Section: Efficacymentioning
confidence: 99%
“…Nine studies (17,21,23,(25)(26)(27)(28)(29)32) were involved in the analysis of safety. The occurrence rate of all-grade and high-grade irAEs were 41% and 13% separately (Table 2).…”
Section: Safetymentioning
confidence: 99%
“…A narrow definition is the resumption of ICI after irAEs improve in patients who stopped treatment due to irAEs (28). A more general definition is the resumption of ICI in patients who stopped treatment for any cause, including the adjustment of specific drugs (29,30). Research has mainly focused on the narrow definition of ICI rechallenge.…”
Section: Discussionmentioning
confidence: 99%